BIOCHEMICAL OXYGEN DEMANDâ€”ITS CHEMICAL REACTION, MATHEMATICAL INTERPRETATION AND METHODOLOGY - Basu, A K (Indian Journal of Fisheries, 2011)
ANY one who studies water pollution and industrial effluents comes across the ever important three wordsâ€”^Biochemical Oxygen Demand, which means the amount of oxygen, in mg., taken up by 1 litre of the sample (usually diluted with sufficient well-oxygenated tap-water or synthetic dilution water made by aerating the distilled water and adding the nutrient salts) or the quantity of dissolved oxygen required to effect stabihsation by aerobic bacterial action that portion of the dissolved organic matter which can be oxidised in 5 days at 20Â° C. It has been observed that in India, Germany and U.S.A. ’ the usual practice is to do B.O.D, tests at 20Â° C. (68Â° F.) but in England most of the B.O.D. experiments are done at 18-3Â° C. (65Â° F.) even though this is giving way to 20Â° C. rapidly. But in practice and interpretation the experiment is not so simple as that. In the present paper a comprehensive attempt to explain the basic methodology, chemistry and kinetics involved in B.O.D. experiment will be made.